Non-traditional Micromachining Processes Fundamentals and Applications - Kibria, Golam; Bhattacharyya, B.; Davim, J. Paulo (Materials Forming, Machining and Tribology, 2017)
This book presents a complete coverage of micromachining processes from their basic material removal phenomena to past and recent research carried by a number of researchers worldwide. Chapters on effective utilization of material resources, improved efficiency, reliability, durability, and cost effectiveness of the products are presented. This book provides the reader with new and recent developments in the field of micromachining and microfabrication of engineering materials.